Literacy dimension in physical education: analysis of construct validity instrument - Kurniawan, Febi; Yuliawan, Dhedhy (Universitas Nusantara PGRI Kediri, 2021)
This research aims to test the dimension of literacy in physical education in students at Singaperbangsa Karawang University. Research is conducted using quantitative approaches with survey methods. The population in this study was all student-athletes in various sports at Singaperbangsa Karawang University which amounted to 721 people. The study sample was determined using proportional random sampling techniques totalling 342 people. The dimensions of physical literacy used are the dimensions of variation and utilization of books (BK), dimensions of variation and use of scientific articles (WM), dimensions of variation and utilization of technology (TECH), and dimensions of environmental variation (LK) . Data analysis used is Confirmatory Factor Analysis (CFA) with Second-Order Confirmation Factor (SOCF) with Lisrel program version 8.80. Data analysis showed that the literacy scale developed for physical learning is a valid and reliable scale and consists of 15 indicators. The dimension of variety and use of writing materials is the most dominant in shaping college student literacy.